Young Consumers' Usability Preferences for Mobile and Computer Screens for Online Shopping Activities. (28th February 2023) - Khan, Shahid Kalim; Khan, Naseer Abbas; Quratulain,; Egorova, Olga; Zia, Nimra; Akhtar, Maria
Abstract : The current research endeavors to investigate and contrast consumer usability preferences in the context of electronic commerce (e-commerce) and mobile commerce (m-commerce) using the theoretical framework of the theory of planned behavior (TPB). In order to distinguish the variations in usability preferences between e-commerce and m-commerce, a survey consisting of 37 items was administered to a sample of 213 young Chinese respondents. The survey is aimed at gathering information pertaining to the usability aspects of these two online shopping platforms. The findings of this research indicate that consumer preferences for m-commerce and e-commerce are contingent on the specific context of online shopping. The results suggest that individuals tend to prefer one medium over the other based on the specific situation or task at hand. This information is valuable for professionals in the fields of marketing, branding, and distribution as it can inform the development of effective strategies for optimizing online presence and revenue. Specifically, knowledge of consumer preferences can assist in the creation of appropriate communication, branding, and distribution strategies tailored to the specific contexts in which consumers are likely to engage in e-commerce and m-commerce.